2022
DOI: 10.3390/nano12081335
|View full text |Cite
|
Sign up to set email alerts
|

Nano Metal-Containing Photocatalysts for the Removal of Volatile Organic Compounds: Doping, Performance, and Mechanisms

Abstract: Volatile organic compounds (VOCs) in indoor air are considered a major threat to human health and environmental safety. The development of applicable technologies for the removal of VOCs is urgently needed. Nowadays, photocatalytic oxidation (PCO) based on metal-containing photocatalysts has been regarded as a promising method. However, unmodified photocatalysts are generally limited in applications because of the narrow light response range and high recombination rate of photo-generated carriers. As a result,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 104 publications
0
1
0
Order By: Relevance
“…In volatile organic compound (VOC) degradation, metal/metal co-dopants, such as silver and vanadium co-doping in TiO 2 nanoparticles, had served a dual role: ensuring uniform metal dispersion on the photocatalyst and creating oxygen vacancies. In the case of non-metal co-dopants, research had demonstrated that co-doping with carbon and nitrogen in TiO 2 can synergistically enhance VOC degradation without altering the catalyst's morphology [142]. However, it is important to note that co-doping may also present challenges, including the potential for enhanced electron-hole pair recombination and nanoparticle shielding effects.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…In volatile organic compound (VOC) degradation, metal/metal co-dopants, such as silver and vanadium co-doping in TiO 2 nanoparticles, had served a dual role: ensuring uniform metal dispersion on the photocatalyst and creating oxygen vacancies. In the case of non-metal co-dopants, research had demonstrated that co-doping with carbon and nitrogen in TiO 2 can synergistically enhance VOC degradation without altering the catalyst's morphology [142]. However, it is important to note that co-doping may also present challenges, including the potential for enhanced electron-hole pair recombination and nanoparticle shielding effects.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Additionally, the stability and recyclability of photocatalysts, as well as the potential toxicity of nanomaterials, need to be carefully addressed and evaluated. Nonetheless, research in the field of photocatalytic degradation continues to advance, focusing on the development of efficient and cost‐effective photocatalytic materials, exploration of alternative light sources, and the optimization of reaction conditions [47–49] . These efforts aim to overcome the drawbacks and limitations of existing treatment methods, providing a sustainable and effective solution for the removal of dyes and other pollutants from wastewater.…”
Section: Introductionmentioning
confidence: 99%